The level of corporate social responsibility practice implementation in selected Malaysian small and medium enterprises / Norhafizah Norbit - Norbit, Norhafizah (2013)
It is important for every company in Malaysia to have the good implementation of corporate social responsibility (CSR) no matter whether the companies are big, medium or small enterprises. Even though it is not mandatory to implement the CSR, many companies have started to implement the CSR practice in their organization, small and medium enterprises (SMEs) should play their role in implementing that CSR practice in their business to ensure the sustainability of their businesses. The CSR is very important in order to achieve that economic sustainability. There are four main objectives of this study that are (i) to examine the level of CSR practice in twenty selected Malaysian SMEs, (ii) to determine the motivation of implementing CSR practices in twenty selected Malaysian SMEs,(iii) to determine the barriers on the implementation of CSR practices in twenty selected Malaysian= SMEs and (iv) to examine the attitude of twenty selected Malaysian SME owners towards CSR practice. This study is based on primary and secondary data. The primary data is from the questionnaires given to twenty selected SMEs and the secondary data is from the Audit Reports of those SMEs. The study is focusing on the SMEs in the Klang Valley areas and in the year of 2012. The analysis will be made on both of the responses from the questionnaire and also from the Detailed Income Statements in the Audit Reports of the selected SMEs